Integrative Analysis of the lncRNA-Associated ceRNA Regulatory Network Response to Hypoxia in Alveolar Type II Epithelial Cells of Tibetan Pigs - Yang, Yanan; Li, Yongqing; Yuan, Haonan; Liu, Xuanbo; Ren, Yue; Gao, Caixia; Jiao, Ting; Cai, Yuan; Zhao, Shengguo (Frontiers in Veterinary Science, 2022)
The function of alveolar type II epithelial (ATII) cells is severely hampered by oxygen deficiency, and understanding the regulatory mechanisms controlling responses to hypoxia may assist in relieving injury induced by hypoxia. In this study, we cultured ATII cells of Tibetan pigs and Landrace pigs under hypoxic and normoxic environments to screen differentially expressed (DE) lncRNAs, DEmiRNAs, and construct their associated ceRNA regulatory networks in response to hypoxia. Enrichment analysis revealed that target genes of DElncRNAs between the normoxic Tibetan and Landrace pig (TN, LN) groups and hypoxic Tibetan and Landrace pig (TL, LL) groups were significantly enriched in proteoglycans in cancer, renal cell carcinoma, and the erbB signaling pathway, and target genes of DEmiRNAs were significantly enriched in axon guidance, focal adhesion, and the MAPK signaling pathway. Hypoxia induction may promote apoptosis through activation of the focal adhesion/PI3K-Akt/glycolysis pathway. The ssc-miR–20b/MSTRG.57127.1/ssc-miR–7-5p axis may play a vital role in alleviating hypoxic injury by regulating ATII cell autophagy between the normoxic and hypoxic groups. MSTRG.14861.4–miR-11971-z–CCDC12 regulated a number of RNAs as the most affected axis, which may regulate ATII cell growth in Tibetan pigs under hypoxic conditions. The ACTA1/ssc-miR-30c-3p/MSTRG.23871.1 axis is a key player in reducing ATII cell injury and improving dysfunction and fibrosis mediated by oxidative stress in Landrace pigs. Our findings provide a deeper understanding of the lncRNA/miRNA/mRNA regulatory mechanisms of Tibetan pigs in hypoxic conditions and assist in the development of strategies to relieve hypoxia-related injury in Landrace pigs.